2019
DOI: 10.1016/j.euromechflu.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

On the early stages of wind-wave generation under accelerated wind conditions

Abstract: a b s t r a c tThe energy and momentum transfer between the atmosphere and the ocean has typically been studied for conditions where the waves have almost or already reached a local equilibrium with a uniform wind. The purpose of this work is to investigate the early stages of the generation of waves under non-stationary wind conditions and to describe the momentum and energy exchange at the airwater interface for non-equilibrium wind conditions. Some experiments with a characteristic wind acceleration were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…That last fact is proof that acceleration magnitude plays a role in limiting wavefield growth under accelerated wind conditions. Wave growth efficiency differences were shown previously in Robles-Diaz et al (2019), where it was observed that under moderate-low and moderate acceleration wind conditions (experiments 2 and 3), the efficiency of the wavefield capturing the available momentum was the highest.…”
Section: Spectral Analysissupporting
confidence: 72%
See 4 more Smart Citations
“…That last fact is proof that acceleration magnitude plays a role in limiting wavefield growth under accelerated wind conditions. Wave growth efficiency differences were shown previously in Robles-Diaz et al (2019), where it was observed that under moderate-low and moderate acceleration wind conditions (experiments 2 and 3), the efficiency of the wavefield capturing the available momentum was the highest.…”
Section: Spectral Analysissupporting
confidence: 72%
“…Apart from the differences in the amount of moment induced by the wind acceleration, the waves showed higher efficiency capturing the air momentum under low, moderate-low, and moderate wind acceleration conditions (experiment 1, 2, and 3), associated with the wavefield characteristics (Robles-Diaz et al, 2019). One characteristic that could induce this high efficiency is the higher wave steepness observed under low, moderate-low, and moderate acceleration wind conditions than higher acceleration wind conditions, as reflected in higher high-frequencies energy levels.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations